TCH-049 Topical Morphine Gels For Painful Wounds. (12th March 2013) - Mateus, D; Trindade, P; Gonçalves, H; Salgado, A; Marto, J; Machado, P; Gouveia, A Melo; Ribeiro, HM; Almeida, A
Abstract : Background: The use of morphine applied topically to painful wounds has potential advantages such as a lower dose than with systemic administration and fewer side effects. Gels are known to be suitable for treating wounds. Purpose: To develop two physicochemically and microbiologically stable gels: a more viscous formulation (F1) and a fluid formulation for spraying (F2), both containing morphine hydrochloride (MH). The effect of viscosity on drug release from both gels was also investigated. Materials and Methods: Sodium carboxymethylcellulose-based aqueous gels were prepared and sterilised by autoclaving. The 0.125% w/w (F1) and 1.0% w/w (F2) gels containing MH were compounded using an injectable solution of MH and preservatives (parabens). Preparation and primary packaging were performed inside a horizontal laminar flow hood. Primary packaging consisted of single dose syringes for F1 and 10 mL amber glass bottles with pump sprays for F2. Stability studies were performed using 3 batches of each final formulation. Samples were stored at 5 ± 3°C, at 22 ± 3°C (light exposed and protected) and 40 ± 2°C/75 ± 5% RH for 98 days (samples collected at 6 time points). Organoleptic characteristics, pH, viscosity, MH and preservative content were assessed. Sterility tests, microbiological control and preservative efficacy were studied according to Ph. Eur. The MH release profile was evaluated using Franz cells. Results: Formulations were odourless, yellowish, translucent and homogeneous. The pH was 6.35 (F1) and 5.70 (F2), viscosity was 52.933 mPa.s at 6.12 s-1 (F1) and 16.7 mPa.s at 12.24 s-1 (F2). Methylparaben, propylparaben and MH contents were between 90–110%. Preservatives were effective and preparations remained sterile and stable for 60 days. MH release was slow and inversely proportional to viscosity. Conclusions: The MH gels presented suitable physicochemical and pharmaceutical characteristics for topical application to painful wounds. The slow release profile may reduce the number of applications. No conflict of interest.